2015
DOI: 10.1039/c5ra00406c
|View full text |Cite
|
Sign up to set email alerts
|

Ordered short channel mesoporous silica modified with 1,3,5-triazine–piperazine as a versatile recyclable basic catalyst for cross-aldol, Knoevenagel and conjugate addition reactions with isatins

Abstract: ARTICLE This journal isAbstract: A triazine-piperazine immobilized on ordered short channel mesoporous silica was synthesized, characterized and used as heterogeneous base catalyst in the synthesis of indole skeletal structure from isatin derivatives under ambient reaction condition in good to excellent isolated yields. The catalyst showed no loss in its efficacy over 10 recycle experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Exactly comparable structures have been obtained from the reactions of isatin itself and benzene‐ring‐substituted isatins . We believe that the sequence (Scheme shows malononitrile and cyclohexane‐1,3‐dione) commences with a Knoevenagel condensation between the reactive isatin 3‐ketone, and the active methylene of the malononitrile, as shown, giving 7 (condensation with the 1,3‐diketone might also be the initiating step – both condensations are known ). Following the condensation, 1,3‐diketone enolate Michael‐type addition to the conjugated system (or malonate anion addition if the first step was condensation with the diketone) generates a second carbon–carbon bond in structure 8 from whence via deprotonation and cyclization involving enolate oxygen addition to one of the nitriles (arrows on 8 ) leads to the final product 4 .…”
Section: Introductionsupporting
confidence: 56%
“…Exactly comparable structures have been obtained from the reactions of isatin itself and benzene‐ring‐substituted isatins . We believe that the sequence (Scheme shows malononitrile and cyclohexane‐1,3‐dione) commences with a Knoevenagel condensation between the reactive isatin 3‐ketone, and the active methylene of the malononitrile, as shown, giving 7 (condensation with the 1,3‐diketone might also be the initiating step – both condensations are known ). Following the condensation, 1,3‐diketone enolate Michael‐type addition to the conjugated system (or malonate anion addition if the first step was condensation with the diketone) generates a second carbon–carbon bond in structure 8 from whence via deprotonation and cyclization involving enolate oxygen addition to one of the nitriles (arrows on 8 ) leads to the final product 4 .…”
Section: Introductionsupporting
confidence: 56%
“…Looking for options for the synthesis of the desired OTCP, it was found that a common method for the preparation of various 3-ylidenemalononitrile derivatives of pyrrol-2-one is the reaction of pyrrole-2,3-diones with malononitrile. [22][23][24] However, such an approach was never used to create any OTCP derivatives. In this regard, at the initial stage, the synthesis of pyrrole-2,3-dione 2 bearing a cyano group in the fourth position, which was necessary for the further creation of the BDTC fragment, was carried out.…”
mentioning
confidence: 99%
“…This reaction was conducted at a low temperature to avoid further substitutions. [48][49][50][51][52][53][54] The next step was the replacement of two other chlorides with N-methylimidazole to produce an ionic liquid (IL) ligand with chlorides as counter ions (MNP@IL/Cl). 48,49 The final step was the exchange of the chloride ions with tungstate to create the final catalyst (MNP@IL/W).…”
Section: Synthesis Of the Mnp@il/w Catalystmentioning
confidence: 99%